Pengaruh Gaya Mengajar Dan Percaya Diri Siswa Terhadap Hasil Belajar Passing Pada Permainan Sepakbola - Usman Tuna (Peneliti.net, 2018)
This study aims to determine the influence of teaching style and confidence in the results of learning passing the ball in the game of football, at MTS Madinatul Furqon Bogor class II 2017/2018. The research method is experiment with treatment design by level 2x2 with sample 32 people. The results of this study are as follows: 1) overall there is a difference between the teaching style of reciprocal and the style of teaching exercise to the learning outcomes of ball passing, 2) for students who have high self-confidence, resirokal teaching style gives better effect than the teaching style exercises on the learning outcomes of ball passing, 3) for students with low self-esteem, the provision of practice-style teaching exercises gives a better effect than the reciprocal teaching style for the learning outcomes of ball passing and 4) there is an interaction between teaching styles with confidence in learning outcomes passing ball.